PENGEMBANGAN INSTRUMEN TES TERTULIS SELEKSI MASUK STAIN PONOROGO TAHUN AKADEMI 2010/2011 - Atho' Fuadi (lp2m-uin malang, 2013)
PENGEMBANGAN INSTRUMEN TES TERTULIS SELEKSI MASUK STAIN PONOROGO TAHUN AKADEMI 2010/2011 Oleh: Athok Fu’adi, M.Pd Dosen STAIN Ponorogo E-mail: athokfuadi@yahoo.com Abstract This research for knowing quality of writen test instruments for STAIN Ponorogo entrance selection in academic year 2010/2011, they are : 1) how validity test is; 2) how far level of difficulty is; 3) how the different power test is; 4) how the validity result analysis, the level of difficulty, different power the test are. This research is quantitatif with the reseach subjects are student applicants and test question. Data is collected by interview and documentation. Sample is taken 10% from all of answer. Validity analysis uses SPSS, while the level of difficulty and different power use microsoft exel programe. The reseach results demonstrate that validity of writen test selection STAIN Ponorogo in academic year 2010/2011 for islamic education is 17 items, for Arabic language is 53 items, for English language is 15 items, and General Knoledge is 25 items, so the validity of the test is very low. Whereas inthe level of difficulty of test instruments for islamic education, Too Difficult (TD) is 16 items, Middle (M) is 39 items, and Too Esasy (TE) is 55 items, for Arabic language Too Difficult (TD) is 25 items, Middle (M) is 69 items, Too Easy (TE) is 6 items, for English language Too Difficult (TD) is 45 items, Middle (M) is 51 items, Too Easy (TE) is 4 items. For general knowledge, Too Difficult (TD) is 18 items, Middle (M) is 46 items, Too Easy (TE) is 36 items. The different power for islamic education, exellent is 0 item, good is 16 items, enough is 41 items, bad is 44 items, very bad is 4 items, so the items were worth at the preserve is on the criteria of excellent, good and enough that are 52 items, for 44 bad items is replaced, and 4 very bad items of this matter should not be issued again the future. 70 items is maintained, while 23 items is replaced , which is 7 items should not be used in the future. Different power for English exellent is 0 item, good is 7 items, enough is 29 items, bad is 43 items, very bad is 20 items, so the items are worth at the preserved there are 36 items, in exchange for 43 points, while 20 points in the future should not be used. Different power general knowledge, exellent is 0 items, 13 items well, 36 items is sufficient, 46 items is bad, 8 items is very bad, then the matter should be maintained 49 items, 46 items are replaced while the 8 items in the future should not be used. Analysis of the validity of a written test on Islamic education is 17%, Arabic is 53%, English is 15%, whereas 25% for general knowledge, it demonstrates the validity of the test is very low for the entrance test STAIN Ponorogo in academic year 2010/2011. Whereas the difficulty level of Islamic Educationis average of 39% is good, 69% for Arabic, 51% for English, 46% for general knowledge, while the good different power for Islamic Education is 52%, 70% for Arabic, 37% for English language, and 49% for general knowledge. Keywords: Test development , test instrument , the University entrance selection